PERAMPASAN DAN PENGEMBALIAN BARANG BUKTI ALAT ANGKUT TINDAK PIDANA ILLEGAL LOGGING DALAM MEWUJUDKAN RASA KEADILAN ( Studi Putusan di Pengadilan Negeri Kandangan, Kabupaten Hulu Sungai Selatan dan Pengadilan Negeri Purbalingga, Kabupaten Purbalingga ) - Praditia Danindra (Jurnal Dinamika Hukum, 2010)
PERAMPASAN DAN PENGEMBALIAN BARANG BUKTI ALAT ANGKUT Studies of Decision Number 14/Pid.B/2006/PN.Kgn jo Number 37/PID/2006/PT.BJM shows that the judge was correct in sentencing, but on the evidence they have different opinions. Courts of first return of the evidence to its owner, while the appeals court that the evidence seized goods for the country. This appeals court decision in accordance with the provisions of Article 78 paragraph (15) of Law Number 41 Year 1999 on Forestry, the Supreme Guide of the Technical Judicial and Court Management in 2005 and the Circular of the Supreme Court (SEMA) No. 01 Year 2008. Here the Panel of Judges to act only as an oral (funnel) laws which in French is called "He boushe de la loi." In Decision Number 44/Pid.B/2009/PN.Pbg jo Number 371/Pid/2009/PT.Smg is already really good against the imposition of the penalty or against the evidence that is returned to the beneficiary even though this decision does not match the above rules . Thus, the High Court Judges Semarang sense of justice is more priority than legal certainty.Keyword: sentencing, evidence, justice, legal certainty, illegal logging.